State-of-the-Art Graphene Synthesis Methods and Environmental Concerns. (2nd February 2023) - Edward, Kaamil; Mamun, Kabir; Narayan, Sumesh; Assaf, Mansour; Rohindra, David; Rathnayake, Upaka
Abstract : Graphene, a 2D sp 2 hybridized carbon sheet consisting of a honeycomb network, is the building block of graphite. Since its discovery in 2004, graphene's exceptional electronic and mechanical properties have peaked interest in various applications. However, the inability to mass produce high-quality graphene affordably currently limits the practical application of the material. Researchers are continuously working on advancing graphene synthesis methods to alleviate these limitations. Therefore, this review looks at the overview of established graphene synthesis methods and characterization techniques, and then highlights an in-depth review of graphene production through flash joule heating. The environmental concerns related to graphene synthesis are also presented in this review paper.